Back to normal symmetry? Biomechanical variables remain more asymmetrical than normal during jump and change-of-direction testing 9 months after anterior cruciate ligament reconstruction - King, E.; Richter, C.; Franklyn-Miller, A.; Wadey, R.; Moran, R.; Strike, S. (The American Journal of Sports Medicine, 2019)
Background: After anterior cruciate ligament reconstruction (ACLR), athletes have demonstrated performance asymmetries as compared with healthy cohorts, but little research has investigated if biomechanical asymmetries are also different during jump and change-of-direction (CoD) tasks between groups. Purpose: To identify if differences in magnitude of asymmetry of biomechanical and performance variables exist between these groups. Study Design: Controlled laboratory study. Methods: Analysis was conducted between 156 male patients 9 months after surgery and 62 healthy participants. Three-dimensional motion capture and analysis were carried out on a double-legged drop jump, a single-legged drop jump, a single-legged hop for distance, and planned and unplanned CoD. Asymmetry between limbs was calculated for each variable with root mean square difference between limbs. Statistical parametric mapping was used to identify the between-group differences in magnitude of asymmetry of performance and biomechanical variables. Results: There were differences in asymmetry of biomechanical variables across all jump and CoD tests, with greater asymmetries in the ACLR group. The majority of differences between groups were in the sagittal and frontal planes, with more differences found in the jump than CoD tests. The single-legged drop jump demonstrated large differences in performance asymmetry (effect size, 0.94) with small differences for both CoD tests (0.4) and none for the single-legged hop for distance. Conclusion: This study demonstrated greater asymmetry of biomechanical variables 9 months after ACLR as compared with healthy participants across all tests, suggesting insufficient rehabilitation. Clinical Relevance: This study highlights the importance of including biomechanical as well as performance variables when assessing rehabilitation status after ACLR.